2020
DOI: 10.1002/bjs.11430
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence following hemithyroidectomy in patients with low- and intermediate-risk papillary thyroid carcinoma

Abstract: Background: This study evaluated the incidence, patterns and risk factors for recurrence after hemithyroidectomy in patients with low-and intermediate-risk papillary thyroid carcinoma (PTC), and verified the predictive role of the risk staging systems in current use. Methods: The clinicopathological characteristics and risk categories were analysed according to recurrence in patients who underwent hemithyroidectomy for low-and intermediate-risk conventional PTC, and were followed up for at least 24 months. Fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…However, it is necessary to investigate the clinical and prognostic implications of multifocality on PTMC, based on the consensus that PTMC has different genetic characteristics, 21 biological behaviour and corresponding clinical management compared with PTC 10,11 . In fact, some studies have focused on the role of multifocality and its bilaterality in the aggression and prognosis of PTMC 7,8,12,13,16,17 . However, some confounding factors, such as sample selection bias and poor matching of baseline characteristics, affect the reliability of the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is necessary to investigate the clinical and prognostic implications of multifocality on PTMC, based on the consensus that PTMC has different genetic characteristics, 21 biological behaviour and corresponding clinical management compared with PTC 10,11 . In fact, some studies have focused on the role of multifocality and its bilaterality in the aggression and prognosis of PTMC 7,8,12,13,16,17 . However, some confounding factors, such as sample selection bias and poor matching of baseline characteristics, affect the reliability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…The American Thyroid Association (ATA) guideline included multifocal PTMC without ETE in the low‐risk category, while ETE was included in the intermediate‐risk category 11 . However, recent studies have shown that multifocality is associated with aggressive progression of the disease (ETE and/or LNM) and impacts the prognosis 7,8,12,13 . Several studies on PTMC and papillary thyroid carcinoma (PTC) have shown that bilateral multifocality accounted for the majority of multifocal cases, 8,9,14,15 and it was an independent predictor for LNM and should be treated aggressively 16,17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the recurrence rate of some low-risk and intermediate-risk PTC patients undergoing hemithyroidectomy is low, the current risk scoring system has no predictive effect on these patients, which needs to be followed up to detect and treat the recurrence early (3). The aggressive clinical pathological, age ≥55, male, tumor size >4 cm, tall cell variant, and positive lymph node metastasis are independent prognostic factors, and there may continue to be the risk of cancer death and early recurrence (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of low mortality, 3-7.9% of patients have loco-regional recurrence within 5 years after initial surgery (5)(6)(7)(8)(9). Of these patients, structural recurrence in the central compartment accounts for 20-55.6% of all loco-regional recurrences (4,7,(9)(10)(11). This proportion of early nodal recurrence reflects the inadequacy of initial surgical management (12,13).…”
Section: Introductionmentioning
confidence: 99%